The Relationship between Providing Covid 19 Incentives, Workload and Interpersonal Relations with the Work Motivation of Nurses in the Inpatient Room of the Regional General Hospital dr. Abdul Rivai - Kiky Sulistiani; Edi Sukamto (Formosa Journal of Applied Sciences, 2023)
The low ratio of health workers in Indonesia compared to other countries is due to the lack of policy development and guarantees for health workers from the government. Factors that can affect the performance or work performance of employees include: motivation, job satisfaction, stress levels, physical condition, work, compensation system and economic aspects. This study aims to determine the relationship between the provision of Covid-19 incentives, workload and interpersonal relations with the work motivation of nurses in the inpatient room of the dr. Abdul Rivai. This type of research is descriptive analytic with cross sectional design with simple random sampling technique in a population of 162 people. The result is that the most dominant influence on motivation is interpersonal relations (p-value) (0.001) than Covid-Intensive Giving (p-value) (0.005)